Combination of Red Clover and Hops Extract Improved Menopause Symptoms in an Ovariectomized Rat Model. (23rd May 2020) - Kim, Mi Ran; Kim, Hyun Jin; Yu, Su Hyun; Lee, Bo Su; Jeon, Se Yeong; Lee, Jeong Jun; Lee, Young Chul
Abstract : Red clover and hops are already known for their alternative menopausal therapies; however, their combination has not yet been studied. This study aimed to evaluate the efficacy of the combination of red clover and hops extract (RHEC) for treating menopausal symptoms for the first time. A high-performance liquid chromatography (HPLC) method for RHEC was developed and validated for the analysis of biochanin A in red clover extract and xanthohumol in hops extract. An in vivo study was conducted using an ovariectomized rat model treated with RHEC (125, 250, and 500 mg/kg, p.o.) for a 12-week test period. Changes in body weight, tail skin temperature (TST), serum lipid profile, bone metabolism, antioxidants, and markers of vasorelaxation and uterus endometrium were evaluated. RHEC significantly inhibited body weight gain and decreased fat weight. Changes in TST associated with flashes were significantly inhibited in the RHEC groups. Other markers related to menopausal symptoms, such as blood lipid profile (total cholesterol and low-density-lipoprotein cholesterol), bone metabolism (serum alkaline phosphatase, osteocalcin, and c-terminal telopeptide type 1), antioxidants (superoxide dismutase and malondialdehyde), and vasorelaxants (endothelin-1 and nitric oxide), were significantly improved after the administration of RHEC. We also confirmed the safety of RHEC through histopathological observation of the endometrium. Our findings demonstrate that RHEC appears to have high potential for comprehensively improving various symptoms of menopause.